2012
DOI: 10.1007/s00345-012-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Parameters derived from the postoperative decline in ultrasensitive PSA improve the prediction of radical prostatectomy outcome

Abstract: Our results demonstrate that the level of PSA nadir and the time to PSA nadir determined by ultrasensitive assay significantly improve the identification of patients who are at high risk of disease recurrence after RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Overall 15% of patients in the high risk treatment group had suspected BCR, lower than the 18% to 32% recurrence rate for patients not receiving TRT after RP during a comparable followup period. 1922 Moreover, the recurrence rate was higher in the high risk treatment group than in the high risk reference group, with no men with BCR in the nonhigh risk subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…Overall 15% of patients in the high risk treatment group had suspected BCR, lower than the 18% to 32% recurrence rate for patients not receiving TRT after RP during a comparable followup period. 1922 Moreover, the recurrence rate was higher in the high risk treatment group than in the high risk reference group, with no men with BCR in the nonhigh risk subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, previous studies have reported TTN as 2.0–3.3 months after RP. 4, 12, 22 If confirmed in future studies, for patients where the early post-operative PSA value is crucial to deciding on adjuvant radiation or not and the PSA is detectable, but below the threshold of recurrence (i.e. ≤0.2 ng/ml), it may be reasonable to give more time for the PSA to decline before documenting a nadir, which may spare some patients from needless radiation.…”
Section: Commentsmentioning
confidence: 88%
“…20 A single-institution study of 319 men found that PSA nadir >0.1 ng/mL and TTN <3 months are independent predictors of BCR. 12 However, the authors did not stratify by both PSA nadir and TTN. When analyzed in our data, we found men with a detectable nadir and a shorter TTN had the greatest risk of BCR.…”
Section: Commentsmentioning
confidence: 90%
See 1 more Smart Citation
“…Two articles used the UCLA‐Prostate Cancer Index (UCLI‐PCI) to assess continence in their cohort. Published in 1998, the UCLA‐PCI was one of the first health‐related QOL tools available to assess men who underwent treatment for prostate cancer . It attempted to more accurately characterize this group of patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%